Studies in law, politics, and society. Vol. 28 - Sarat, Austin; Ewick, Patricia (Amsterdam : Elsevier JAI, 2003)
Description: This volume presents articles by an interdisciplinary and international group of scholars spanning the social sciences, humanities, and law. It offers new perspectives on political relationships, politics, legal reform, law and the family, race relations and gender issues.
Issues in constitutional interpretation. Revisiting constitutional interpretation : a comparative perspective on the American debates / Matthew J. Moore -- Minority representation, the Supreme Court, and the politics of democracy / Yasmin A. Dawood. "Missing persons". Accounting for absent bodies : the politics and jurisprudence of the Missing Persons Act / Thomas M. Hawley -- Surviving law : death community culture / Patrick Hanafin -- Extraterritorial criminal jurisdiction : replacing "objective territoriality" with "defensive territoriality" / Ellen S. Podgor. The challenges of (and to) rights. "Subjectivity is a citizen" : representation, recognition, and the deconstruction of civil rights / Jonathan Goldberg-Hiller.
Includes bibliographical references.
Description based on print version record.
Keywords: Punishment -- Philosophy; Criminal law -- Philosophy; Criminals -- Public opinion; Imprisonment -- Social aspects; Imprisonment -- Moral and ethical aspects; Criminals -- Rehabilitation; Law & society; Law -- General